1992
DOI: 10.1017/s1041610292001005
|View full text |Cite
|
Sign up to set email alerts
|

Personality in Recovered Depressed Elderly

Abstract: Personality traits in euthymic elderly subjects with and without past histories of major depressive episodes were assessed using the Structured Clinical Interview for DSM-III-R and the Social Adjustment Scale-SR. Recovered depressed subjects were characterized by significantly more personality traits from DSM-III-R Clusters B and C than controls, and they exhibited differences in social adjustment, as well. Subjects who have recovered from depressive episodes may show significant diferences in personality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Other age and cohort effects may further obscure the meaning of personality data drawn from heterogeneous populations (Gynther, 1979). Of interest here are the observations that involutional depressives had specific patterns of personality difficulty (Titley, 1936), while geriatric depressives had more diffusely dysfunctional personalities (Vispo, 1962;Abrams et al, 1987;Schneider et al, 1987). The present findings suggest an association between neuroticism and geriatric depression.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Other age and cohort effects may further obscure the meaning of personality data drawn from heterogeneous populations (Gynther, 1979). Of interest here are the observations that involutional depressives had specific patterns of personality difficulty (Titley, 1936), while geriatric depressives had more diffusely dysfunctional personalities (Vispo, 1962;Abrams et al, 1987;Schneider et al, 1987). The present findings suggest an association between neuroticism and geriatric depression.…”
Section: Discussionsupporting
confidence: 47%
“…Using the Personality Disorder Examination (PDE), a recently developed structured interview for diagnosing DSM-111-R personality disorders (Loranger et al, 1987), we found that recovered elderly depressives had higher dimensional scores for all DSM-111-R personality disorders except antisocial personality (Abrams et al, 1987). Schneider et al (1987) reported that twice as many recovered elderly depressives met full criteria for DSM-111-R personality diagnoses as normal controls.…”
mentioning
confidence: 99%
“…T he possible influences of personality traits or disorders on the etiology of geriatric depression have long been of interest to clinicians, often with the assumption that some personality features predispose individuals to develop depression in late life. 1 -4 In several studies, geriatric depressives have been reported to have more lifetime personality dysfunction, according to DSM-III-R personality disorder criteria, than normal elderly subjects.t- 6 However, this area has remained largely speculative, and new developments in the study of geriatric depression make it timely to reexamine them. Recent data suggest that geriatric depression comprises a heterogeneous group of disorders and that clinical and biological parameters may distinguish geriatric depression with onset in late life from geriatric depression with earlier onset.…”
mentioning
confidence: 99%
“…The studies varied greatly in terms of the comorbidity of major depression, with some s t u d i e s i n c l u d i n g o n l y d e p r e s s e d i n d i v i d u a l s [13,15,37,40,41] and other studies comparing depressed samples with other samples (nondepressed [42], or other Axis I [22]), others not indicating Axis I comorbidity at all [43,44], and the remainder indicating some comorbid depression in their sample. As all three studies comparing depressed patients with nondepressed patients found that the presence of major depression increased the prevalence of personality disorder diagnoses, it seems important to add this information to later meta-analyses [21,42,45]. In addition, one of the studies added in the second metaanalysis included respondents aged 42 to 65, all of whom were depressed [41].…”
Section: Study Featurementioning
confidence: 99%